Syntheses, crystal structures, and DNA-binding properties of two nickel(II) complexes with 1, 3-bis(benzimidazol-2-yl)-2-oxapropane derivatives. Issue 10 (18th May 2016) - Zhang, Han; Wu, Huilu; Chen, Chengyong; Zhang, Jiawen; Yang, Zaihui; Peng, Hongping; Wang, Fei
Abstract: [Ni(obb)(DMF)2 (H2 O)]·(Pic)2 ·0.5DMF (1 ) and [Ni(Etobb)2 ]·(Pic)2 ·2DMF (2 ) (obb = 1, 3-bis(benzimidazol-2-yl)-2-oxapropane, Etobb = 1, 3-bis(1-ethylbenzimidazol-2-yl)-2-oxapropane, Pic = picrate) have been synthesized and characterized by physicochemical and spectroscopic methods. The structures of both complexes have been determined by X-ray single-crystal diffraction. The coordination geometries of1 and2 can be described as distorted octahedra. The interaction of the nickel(II) complexes with calf thymus DNA was investigated by electronic absorption, fluorescence spectroscopy, and viscosity measurements. The experimental results suggest that1 and2 bind to DNA in an intercalation mode, and their binding affinity for DNA follows the order1 > 2 . DNA-binding behaviors can be attributed to the large coplanar aromatic rings in the V-shaped ligand and steric hindrance. Abstract :